Epidemiologické hodnocení elektroforetypů rotavirů u dĕtí hospitalizovaných s průjmem ve fakultní nemocnici v Plzni v letech 1987-1989 - Pazdiora, P; Tietzová, J (Ceskoslovenska epidemiologie, mikrobiologie, imunologie, 1993)
During 1987-1989 the authors investigated by electrophoresis in a polyacrylamide gel (PAGE) the circulation of rotavirus electropherotypes in younger children admitted with diarrhoeal diseases to the infectious and paediatric clinic of the Faculty Hospital in Plzen. From 275 specimens of faeces with evidence of rotaviruses the electropherotype was assessed in 165 cases (60%). During the investigation period among the children five basic electropherotypes circulated. The authors did not reveal a predominance of a certain type. In the aetiology of 24 nosocomial infections, where the electropherotype was diagnosed, only types were represented found during the appropriate period in children admitted to the investigated department.
Keywords: kojenec; Infant; Rotavirus; rotavirové infekce; novorozenec; Rotavirus Infections; Electrophoresis, Polyacrylamide Gel; lidé; Humans; Diarrhea, Infantile; elektroforéza v polyakrylamidovém gelu; průjem kojenců; Infant, Newborn